2021
DOI: 10.1111/cas.14896
|View full text |Cite
|
Sign up to set email alerts
|

H19 promotes aerobic glycolysis, proliferation, and immune escape of gastric cancer cells through the microRNA‐519d‐3p/lactate dehydrogenase A axis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…revealed that overexpression of H19 promotes immune escape of GC cells by modulating the activity of immune cells (γδT cells, Jurkat cells, and TAMs) via miR-519d-3p/LDHA axis. 134 Moreover, upregulation of SNHG15 is reported to increase the expression of PDL1 by targeting miR-141, thus facilitating the immune escape of GC cells. 135 In contrast to these oncogenic lncRNAs, some anti-tumoral lncRNAs show the opposite effect on the immune escape of GC cells.…”
Section: Roles Of Lncrnas In Gcmentioning
confidence: 99%
“…revealed that overexpression of H19 promotes immune escape of GC cells by modulating the activity of immune cells (γδT cells, Jurkat cells, and TAMs) via miR-519d-3p/LDHA axis. 134 Moreover, upregulation of SNHG15 is reported to increase the expression of PDL1 by targeting miR-141, thus facilitating the immune escape of GC cells. 135 In contrast to these oncogenic lncRNAs, some anti-tumoral lncRNAs show the opposite effect on the immune escape of GC cells.…”
Section: Roles Of Lncrnas In Gcmentioning
confidence: 99%
“… 5 For the Warburg effect, glucose is the substrate and lactate is the end product, thus, glucose consumption and lactate production could be used as parameters of aerobic glycolysis. 6 8 The Warburg effect not only furnishes cancer cells with ATP and anabolic precursors for macromolecules but also provides an acidic environment which could promote local invasion and proliferation of cancer cells. 9 , 10 Because of the important role of the Warburg effect in tumor growth and progression, hunting for the Warburg effect-related therapeutic targets has important value.…”
Section: Introductionmentioning
confidence: 99%
“…hsa-miR-519d-3p was predicted to target CDKN1A, HIF1A, MXD1 , and SOD2 , and its expression was significantly downregulated in COPD. Previous studies have reported that hsa-miR-519d-3p is involved in tumorigenesis in gastric cancer, pancreatic cancer, and lung cancer [ 52 54 ], and correlates with cell proliferation and migration in trophoblastic cell lines [ 55 ]. The biological function of hsa-miR-519d-3p in COPD is unknown.…”
Section: Discussionmentioning
confidence: 99%